Italians on the Age of COVID-19: The Self-Reported Depressive Symptoms Through Web-Based Survey - Balsamo, Michela; Carlucci, Leonardo (Frontiers in Psychology, 2020)
Pandemic of Coronavirus Disease 2019 (COVID-19) had been damaging the Italian 3 community. The widespread use of quarantine is having the desired impact of controlling the 4 epidemic, although presents many psychological consequences. 5 To date, compliance of the Italian public with voluntary home quarantine has been very high, but 6 little is known about the impact of mental health during the pandemic. The purposes of this study 7 were to assess the prevalence of depressive symptoms during lockdown and the potential factors that 8 contribute to, or mitigate, these effects. 9 During the very early stage of the nationwide lockdown, a total of 3672 Italian quarantined 10 self-selected adult residents (65% females, range 18-85 years) participated in a web-based cross-11 sectional survey, including measures of depressive symptoms (Teate Depression Inventory) and 12 anxiety. The overall prevalence were27.8% for moderate and 9.3% for severe levels of depressive 13 symptoms. Generalized Logistic Model was used to identify the factors associated with mental health 14 problems. Among these factors, socio-demographic variables (e.g. sex, age, employment status) and 15 adherence to quarantine guidelines were analyzed. Females, youngest people, students, singles, 16 residents in Northern Italy and people less adherent to quarantine guidelines and less worried about 17 being infected with COVID-19 pandemic were at a high risk of developing depressive symptoms 18 during COVID-19 epidemic, also after controlling for anxiety state. These findings showed that 19 public levels of depressive symptoms did not increase to the greater likelihood of being infected. Our 20 study suggested that continuous surveillance and monitoring of the psychological consequences for 21 outbreaks should identify which groups at higher risk of psychological morbidities due to the current 22 pandemic in order to target future psychological interventions to be implemented.